2013
DOI: 10.1378/chest.13-0183
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Left Ventricular Filling in COPD and Emphysema: Is It the Heart or the Lungs?

Abstract: 1143C hronic lower respiratory disease is the third-leading cause of death in the United States. 1 The most morbid components of chronic lower respiratory dis ease are COPD, defi ned by spirometry as airfl ow obstruction that is not fully reversible, and pulmonary emphysema, defi ned by morphology as permanent enlargement of airspaces accompanied by destruction of their walls. 2,3 Emphysema on CT imaging is present in approximately one-half of patients with COPD, 4-7 and an estimated 2% of the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 51 publications
7
49
1
7
Order By: Relevance
“…Our observation that a greater decline in the FEV 1 /FVC ratio is associated with an underfilled/low-output cardiac phenotype at Year 25 is compatible with the findings of early vascular changes seen in the animal model. Reduced pulmonary vein area has been described in individuals with established COPD suggesting an "upstream" obstruction to blood flow as the cause of reduced LV preload (32). Our findings indicate that the development of an under-filled left heart occurs concurrent with the decline in lung (33,34).…”
Section: Original Articlesupporting
confidence: 55%
“…Our observation that a greater decline in the FEV 1 /FVC ratio is associated with an underfilled/low-output cardiac phenotype at Year 25 is compatible with the findings of early vascular changes seen in the animal model. Reduced pulmonary vein area has been described in individuals with established COPD suggesting an "upstream" obstruction to blood flow as the cause of reduced LV preload (32). Our findings indicate that the development of an under-filled left heart occurs concurrent with the decline in lung (33,34).…”
Section: Original Articlesupporting
confidence: 55%
“…Particularly, a higher vascular resistance in COPD leads to increased right heart load [21] that usually considered as cor pulmonale and impaired filling of the LV [22,23]. In turn, structural pulmonary changes occur in chronic left heart failure.…”
Section: Heart and Lung Interactionsmentioning
confidence: 99%
“…Underfilling of the LA has also been shown in patients with COPD [19]. Moreover, it was previously demonstrated via magnetic resonance angiography that the pulmonic vein area of patients with COPD is smaller, suggesting underfilling of their LA [20]. Proposed mechanisms for decreased left side filling in patients with COPD include an altered intrathoracic pressure, increased pulmonary veins resistance, compression of alveolar vessels [20], increased heart rate [19], systemic vasodilation [21], and bulging of the septum due to right heart dilatation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was previously demonstrated via magnetic resonance angiography that the pulmonic vein area of patients with COPD is smaller, suggesting underfilling of their LA [20]. Proposed mechanisms for decreased left side filling in patients with COPD include an altered intrathoracic pressure, increased pulmonary veins resistance, compression of alveolar vessels [20], increased heart rate [19], systemic vasodilation [21], and bulging of the septum due to right heart dilatation [22,23]. Investigating the etiologies of small LA size on CT, Cassagnes et al [6] reported that patients with emphysema had an inverse correlation between LA volume and the severity of emphysema.…”
Section: Discussionmentioning
confidence: 99%